2015
DOI: 10.1016/j.str.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Gating Topology of the Proton-Coupled Oligopeptide Symporters

Abstract: SummaryProton-coupled oligopeptide transporters belong to the major facilitator superfamily (MFS) of membrane transporters. Recent crystal structures suggest the MFS fold facilitates transport through rearrangement of their two six-helix bundles around a central ligand binding site; how this is achieved, however, is poorly understood. Using modeling, molecular dynamics, crystallography, functional assays, and site-directed spin labeling combined with double electron-electron resonance (DEER) spectroscopy, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
161
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(182 citation statements)
references
References 51 publications
(94 reference statements)
12
161
2
Order By: Relevance
“…S2B). The involvement of residues from TM5 and TM11 in the cytoplasmic gate of other MFS transporters (32,(37)(38)(39)(40) is consistent with this proposed role.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…S2B). The involvement of residues from TM5 and TM11 in the cytoplasmic gate of other MFS transporters (32,(37)(38)(39)(40) is consistent with this proposed role.…”
Section: Discussionsupporting
confidence: 78%
“…S2). A recent study that analyzed all available crystal structures in the MFS concluded that the cytoplasmic gate is formed by residues in TMs 4, 5, 10, and 11 (32). This led us to test the hypothesis that the above network of interactions connecting the cytoplasmic ends of TM5 and TM11 contributes to the cytoplasmic gate in VMAT2.…”
Section: Homology Modeling Predicts That Y423 Contributes To the Cytomentioning
confidence: 97%
“…Essentially, the authors showed that through careful sequence alignment and structure threading, the sequence of each 3-TM inverted topology repeat unit could be transposed onto the symmetrically equivalent unit, which in the case of the MFS turns out to be A-C and B-D. The subsequent outward open state, which had previously been recalcitrant to crystallisation, was subsequently determined and shown to agree, at least qualitatively, with the "repeat-swapped" model [27]. The conceptual advance in this work was the realisation that a "symmetry-exchange" mechanism underlies the overall conformational change with the MFS and has been shown, more broadly, to operate within all currently determined secondary active transporter families [20].…”
Section: Symmetry-exchange Underlies the Overall Conformational Changmentioning
confidence: 97%
“…Recently we used the repeat swapped methodology to propose a 'gating' topology for how POT transporters move between inward and outward facing states in response to proton and peptide binding [27]. To occlude the peptide binding site to either side of the membrane, POT transporters form gates, which are transient constrictions formed by the close packing of several transmembrane helices.…”
Section: Gating Topology With the Pot Familymentioning
confidence: 99%
See 1 more Smart Citation